Mind the climate policy gaps: climate change public policy and reality in Portugal, Spain and Morocco - Camargo, J.; Barcena, I.; Soares, P. M.; Schmidt, L.; Andaluz, J. (Climatic Change, 2020)
The IPCC 1.5 °C report argues for a 50% cut of global greenhouse gas emissions by 2030. Dangerous gaps lie between what is required to reach the 1.5 °C objective, what governments have pledged and what is happening in reality. Here, we develop ‘climate policy gap’ graphics for Portugal, Spain and Morocco to help reveal this divide and quantify the under-reaction between diagnosis and action, through layers of political intended and unintended miscommunication, insufficient action and the power of the fossil fuels industries. The climate policy gaps for the three nations reveal overshoots on even the most ambitious levels of emissions reductions pledged when compared with trajectories compatible with 1.5 °C or even 2 °C limits. This research suggests that there is a built-in feature of under-reaction in climate policy, which staves off any emission pathways compatible with stopping a temperature rise above 1.5 °C by 2100. It shows that the climate policy gap is a political and methodological tool that reveals systemic shortcomings of government climate action. Its visibility identifies benchmarks and sectors that should be activated to close these gaps in response to the growing popular demands for climate justice.